Revision of the New Zealand gecko genus Hoplodactylus, with the description of a new species - Scarsbrook, Lachie; Walton, Kerry; Rawlence, Nicolas J.; Hitchmough, Rodney A. (Zootaxa, 2023)
The New Zealand endemic gecko genus Hoplodactylus is revised. Two species are recognized: Hoplodactylus duvaucelii (Duméril & Bibron, 1836) from the North Island and some near-shore islands, and H. tohu n. sp., which was formerly widespread throughout the South Island but is presently restricted to some islands in the Cook Strait region. H. delcourti (Bauer & Russell, 1986) is retained in Hoplodactylus sensu lato in the interest of taxonomic stability, pending further research, but is probably neither congeneric nor from New Zealand.